TINJAUAN DENSITAS RADIOGRAF PADA BERBAGAI KETEBALAN STEP WEDGE BERBASIS VARIASI ARUS TABUNG - Nuramdiani, Dian; Sarengat, Sarengat; Maulana, Iman (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
This research aimed to review the density of radiographs with different variations of tube currents. It was conducted at the Radiology Laboratory of Al Islam Polytechnic of Bandung. This study is an optimization of the results of the X-ray machine examination in order to produce good quality images with the smallest possible radiation given to the patient within a safe limit value. Exposures were carried out on the step wedge with different tube currents of 5 mAs, 8 mAs, 10 mAs, 12.5 mAs, and 80 kV voltage, as well as the exposure time of 0.05 second which was set as a constant variable. The measurement results showed that the greater the tube currents were, the greater the measured density value would be. In accordance with the thickness of the material passed by the X-rays, the thicker the material was, the smaller the value of the measured density would be. Furthermore, among different selected tube currents, the tube current value of 5 mAs became the optimal value. It was indicated by the coefficient of determination between the tube current and the radiographic density value of 0.9842. However, other tube current variations were also more than 0.90. Consequently, it can be concluded that current values will greatly affect the density value of radiographs.